1999
DOI: 10.1177/1077559599004001002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors Associated with Sexually Abused Children's Psychosocial Adjustment

Abstract: The potential influence of maternal adjustment and parenting style on children's psychological adjustment following sexual abuse was examined. A battery of standardized parent and child self-report instruments were administered to 100 sexually abused children and their nonoffending mothers. The results of a series of multiple regression analyses indicated that the maternal self-reported depression significantly contributed to the expression of both post-traumatic stress disorder (PTSD) symptoms and parent-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…Further, when a victim perceived that his/her mother was rejecting, greater depressive symptoms were reported. Similarly, those victims that reported that their mother utilized parenting styles that were guilt triggering were more likely to report symptoms of PTSD (Deblinger et al, 1999). There is no way to discover a causal relationship between maternal depression and child's outcome, and the results may be due to the parent reporting greater symptoms in their children due to their own psychological distress, or that the children, through their interactions with depressed parents, develop more psychological symptoms than their peers (Deblinger et al, 1999).…”
Section: Parental Distress Mental Health and Copingmentioning
confidence: 67%
See 3 more Smart Citations
“…Further, when a victim perceived that his/her mother was rejecting, greater depressive symptoms were reported. Similarly, those victims that reported that their mother utilized parenting styles that were guilt triggering were more likely to report symptoms of PTSD (Deblinger et al, 1999). There is no way to discover a causal relationship between maternal depression and child's outcome, and the results may be due to the parent reporting greater symptoms in their children due to their own psychological distress, or that the children, through their interactions with depressed parents, develop more psychological symptoms than their peers (Deblinger et al, 1999).…”
Section: Parental Distress Mental Health and Copingmentioning
confidence: 67%
“…Some researchers feel that the family environment, including a parent's response to the disclosure of CSA and the support given to the victim, is potentially more influential on outcome than the factors related to the abuse itself, if only because these family variables are potential targets for intervention, whereas the abuse characteristics are immutable (Deblinger, Steer, & Lippman, 1999). In general, the literature suggests that victims who receive support from their nonoffending parents are less symptomatic than those victims that receive no support.…”
Section: Parental Reaction To Disclosure/support Of the Victimmentioning
confidence: 95%
See 2 more Smart Citations
“…Parents may have the most significant influence on how children understand their experiences. In fact, it has been well documented that parental rejection or distress following an abusive experience may negatively influence postabuse recovery (Cohen & Mannarino, 2000;Deblinger, Steer, & Lippmann, 1999).…”
Section: Messages In the Aftermath Of Abuse That May Reinforce Feelinmentioning
confidence: 99%